A Putty-Clay Model of Demand Uncertainty and Investment - James W. Albrecht; Albert G. Hart (The Research Institute of Industrial Economics (IUI), 1979)
This paper uses a simple model to explore the effects of 'increasing demand risk' on business fixed investment. We show that within a putty-clay framework an increase in demand uncertainty can be expected to have two countervailing effects. On the one hand increasing risk tends to induce a firm to increase its capacity, but on the other hand the optimal capital intensity of that capacity decreases.
Keywords: D92; L11; 330; Firm investment; Firm strategy; Production